Association of vitamin D, retinol and zinc deficiencies with stunting in toddlers: findings from a national study in Iran. (April 2020) - Sharif, Y.; Sadeghi, O.; Dorosty, A.; Siassi, F.; Jalali, M.; Djazayery, A.; Shokri, A.; Mohammad, K.; Parsaeian, M.; Abdollahi, Z.; Heshmat, R.; Yarparvar, A.; et al.
Abstract: Objective: The objective of this study was to investigate the association of serum levels of 25(OH)D3 (vitamin D), retinol (vitamin A) and zinc with stunting in a large sample of Iranian toddlers. Study design: This was a cross-sectional study. Methods: A total of 4261 children, aged 10–36 months, who had Iranian birth certificates were included in the present study. Weight and height were measured by experienced professionals in accordance with standard protocols. Stunting was defined as a height-for-age z-score of <-1 standard deviation (SD) based on the World Health Organization (WHO) criteria (the WHO Child Growth Standards median). Serum levels of 25(OH)D3, retinol and zinc were examined based on standard methods. Results: The mean age of the study participants was 19.2 ± 8.4 months. A significant inverse association was found between serum retinol concentrations and the odds of stunting such that after controlling for potential confounders, toddlers in the highest quartile of serum retinol levels had 29% lower odds of stunting than those in the lowest quartile (odds ratio [OR]: 0.71, 95% confidence interval [CI]: 0.53–0.97). Furthermore, a significant inverse association was found between serum levels of retinol and stunting in girls (OR: 0.57, 95% CI: 0.34–0.94), urban toddlers (OR: 0.66, 95% CI: 0.44–0.99) and those who did not use nutritional supplements (OR: 0.70, 95% CI: 0.52–0.95). Although serum 25(OH)D3 levels were not significantly associated with stunting in the overall study population, we found a positive association among toddlers who used nutritional supplements. No significant association was found between serum levels of zinc and stunting. Conclusion: We found a significant inverse association between serum levels of retinol and stunting in toddlers aged 10–36 months. Highlights: There is a significant inverse association between serum levels of retinol (vitamin A) and stunting in Iranian toddlers. This inverse association of retinol and stunting is particularly evident in girls and urban toddlers. Serum levels of vitamin D and zinc were not significantly associated with stunting.